Assessment of Patient's Knowledge and Practice Regarding their Diabetic Foot in Chamchamal District (AL- Slemani City) - Samir Y. Lafi; Hawar Mardan Mohammad (Kufa Journal for Nursing Sciences)
Background: Diabetic foot is common in the diabetic population; it is one of the most incapacitating chronic Complications resulting in poor disease management.